Did Thomas Know the Synoptic Gospels?: A Response to Denzey Lewis, Kloppenborg and Patterson - Goodacre, Mark S. (Journal for the study of the New Testament, 2014)
Nicola Denzey Lewis, Stephen Patterson and John Kloppenborg have written appreciative but critical reviews of the books by Simon Gathercole and Mark Goodacre. This response focuses on several key elements in their critiques: Thomas’s role in second- and fourth-century Christianity; the difference between ‘direct links’ and ‘diagnostic shards’; the analogy of ‘the plagiarist’s charter’; the categories ‘secondary orality’ and ‘scribal culture’; the role played by oral tradition; the argument from Thomas’s genre; the example of the Rich Fool; modelling Christian origins; and questioning the notion of a ‘new Synoptic Problem’.